The symmetric and asymmetric effect of financial development on ecological footprint in South Africa: ARDL and NARDL approach - Khoza, Sibusiso; Biyase, Mduduzi (Frontiers in Environmental Science, 2024)
The literature on finance-emission nexus offers conflicting conclusions. This study resolves this inconsistency by investigating the symmetric and asymmetric effect of financial development on ecological footprint in South Africa, using the Environmental Kuznets Curve framework as a guide. Given the coexistence of ecological deficits and world-class financial development systems in South Africa, it is essential to explore and evaluate potential solutions to mitigate these deficits. Our empirical analysis contribute to the body of literature on the impact of financial development and ecological footprint by using comprehensive measure of financial development and disaggregated it into its sub-indices to provide a rather nuanced analysis. It also relies upon the linear auto regressive distribution lag (ARDL) and nonlinear auto regressive distribution lag (NARDL) technique to explore the complex interactions of financial development and ecological footprint. The findings of this research indicate that financial markets and financial institutions seem to have varying effects on ecological footprint. It was found that financial markets indices promote environmental quality, while financial institutions exacerbate environmental quality. These results call for policymakers to craft a watertight process that will encourage both financial markets and financial institutions to allocate capital to projects that are pro-environmental.No.